Revisiting the role of h2o2 in nrf2 activation using an oxygen-independent biosensor - Miri, Seyed Mohammad; Eroğlu, Emrah (My University, 2024)
[Abstract Not Available]
Keywords: Biochemistry; Molecular Biology; Endocrinology; Metabolism